Pengembangan E-LKPD Berbasis Socio-Scientific Issues (SSI) untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa SMP - Dinnar Lambang Kinasih; Ulin Nuha; Firdha Yusmar (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
Junior high school students' problem-solving skills in science learning are relatively low due to a lack of innovation and variety in learning media. The purpose of this study was to develop SSI-based E-LKPD as an innovative learning media that is valid, practical, and effective in honing and improving junior high school students' problem-solving skills. This study used a Research & Development (R&D) research design with reference to the ADDIE model. The location of this study was SMPN 4 Tanggul with 32 eighth-grade students as research subjects. Data collection was conducted using validation sheets, learning implementation observation sheets, pretest and posttest, and student response questionnaires. The results showed that SSI-based E-LKPD is valid for use with an average validity score of 92.77% in the highly valid category. The practicality of using SSI-based E-LKPD showed an average score of 93.75% in the highly practical category. The effectiveness test showed an N-gain score of 0.66, categorized as moderate. Student responses received an average score of 88.7%, categorized as very good. Based on these results, it can be concluded that the SSI-based E-LKPD developed is valid, practical, and effective in improving the problem-solving skills of junior high school students.